Silver linings for the elderly in the Philippines: Policies and programs for senior citizens - Celia M. Reyes; Arkin A. Arboneda; Ronina D. Asis (Philippine Institute for Development Studies (PIDS), 2019)
The Philippines is identified as one of the countries with an ageing population, as the proportion of persons aged 60 and above is at 7.4 percent in 2015 and is projected to increase to 15.9 percent by 2045. Senior citizens tend to have higher prevalence of various medical diseases and comorbidities. Moreover, they are less economically active compared to younger age groups. Thus, this projected increase in the number of senior citizens entails greater support needed in terms of health care and income security for the elderly. In response to this, the government has been enacting various legislations and implementing various social protection programs for senior citizens. Among the following are the mandatory coverage of senior citizens to PhilHealth, and retirement benefits and pension through SSS and GSIS for senior citizens previously involved in the formal economy, or through the social pension program for indigent senior citizens.
Keywords: 330; Ageing population; senior citizen; social protection; social pension; Philippines